2017
DOI: 10.4103/0259-1162.184613
|View full text |Cite
|
Sign up to set email alerts
|

Obturator nerve block in transurethral resection of bladder tumor: A comparative study by two techniques

Abstract: Context:Sparing of obturator nerve is a common problem encountered during transurethral resection of bladder tumor (TURBT) under spinal anesthesia.Aims:To evaluate and compare obturator nerve block (ONB) by two different techniques during TURBT.Settings and Design:This is prospective observational study.Subjects and Methods:Forty adult male patients from the American Society of Anesthesiologists Class I–IV planned to undergo TURBT under spinal anesthesia were divided into two groups of twenty each. In one grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Anatomically, the obturator nerve arises from the anterior thigh of the anterior branch of L 2– L 4 and enters the minor pelvis after the medial border of the psoas muscle comes out; it progresses along the lateral wall of the minor pelvis and protrudes from the obturator canal from the minor pelvis to the thigh, dividing the anterior and posterior branches, and enters the thigh adductor muscle group through the anterior and posterior adductor brevis muscles; during the course of the obturator nerve, it abuts the bladder neck, lateral bladder wall, and prostatic urethra [ 18 ]. Therefore, when TURBT is performed in patients with lateral bladder wall tumors, obturator nerve reflexes often occur due to induced current stimulating the adjacent obturator nerve, which causes involuntary spasms or even sudden and intense movement of the thigh adductor muscle, resulting in bladder perforation, massive hemorrhage, abdominal organ injury, and extravesical spread of the tumor [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the obturator nerve arises from the anterior thigh of the anterior branch of L 2– L 4 and enters the minor pelvis after the medial border of the psoas muscle comes out; it progresses along the lateral wall of the minor pelvis and protrudes from the obturator canal from the minor pelvis to the thigh, dividing the anterior and posterior branches, and enters the thigh adductor muscle group through the anterior and posterior adductor brevis muscles; during the course of the obturator nerve, it abuts the bladder neck, lateral bladder wall, and prostatic urethra [ 18 ]. Therefore, when TURBT is performed in patients with lateral bladder wall tumors, obturator nerve reflexes often occur due to induced current stimulating the adjacent obturator nerve, which causes involuntary spasms or even sudden and intense movement of the thigh adductor muscle, resulting in bladder perforation, massive hemorrhage, abdominal organ injury, and extravesical spread of the tumor [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obturator nerve block (ONB) is widely used to prevent contractions and sudden movements of thigh adductor muscles during transurethral resection operations of bladder tumor and to relieve adductor muscle spasms in patients with spasticity, to treat chronic hip pain and to improve persistent hip adductor spasticity in patients with paraplegia, for postoperative analgesia in femoral operations, to provide optimal analgesia for patients and to treat pain after hip and knee surgery [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al [12] compared ONB performed via a nerve stimulator under spinal anesthesia, to a transvesical approach. They found a statistically significant difference between the groups with regards to the occurrence of obturator jerk, and concluded that blocks performed using a nerve locator appeared to be more effective than a transvesical approach.…”
Section: Obturator Nerve Block (Onb)mentioning
confidence: 99%
“…Therefore, avoiding overfilling of the bladder reduces the risk of obturator nerve stimulation. Various other strategies have also been described, such as resecting the tumor on thinner slices, laser resection, reversing the polarity of the diathermy current, and changing the site of the inactive electrode [12]. …”
Section: Preventing “Obturator Jerk”mentioning
confidence: 99%